Catastrophe remembered : Palestine, Israel and the internal refugees : essays in memory of Edward W. Said (1935-2003) - Masalha, Nur (Zed Books ; Distributed in the USA by Palgrave Macmillan, 2005)
The 1948 Palestine War is known to Israelis as 'the War of Independence'. But for Palestinians, the war is forever the Nakba, the 'catastrophe'. The war led to the creation of the State of Israel and the destruction of much of Palestininan society by the Zionist forces. For all Palestinians, the Nakba has become central to history, memory and identity. This book focuses on Palestinian internal refugees in Israel and internally displaced Palestinians across the Green LIne. It uses oral history and interviews to examine Palestinian identity and memory, indigenous rights, international protection, the 'right of return', and a just solution in Palestine/Israel.